Food tourism a practical marketing guide - Stanley, John; Stanley, Linda (CABI, 2015)
The fastest growth in tourism is the culinary sector. Covering farmers markets, agri-entertainment, glamping, restaurants, farm shops and more, food tourism is both an important part of holidaying and a purpose in itself. This book provides an overall direction to the development of food tourism and a section on the future of this trend.